Initial Experience with Novel Single-Use Disposable Ureteroscopy: A Prospective, Single Arm 90-Day Trial of the Axis Ureteroscope. Issue 2 (4th March 2021) - Large, Tim; Rivera, Marcelino; Nottingham, Charles; Agarwal, Deepak; Mellon, Matthew; Krambeck, Amy
Abstract: Introduction: Novel digital disposable ureteroscopes are becoming more commonplace in endourological practices. We trialed the Axis™ single-use ureteroscope, which is distributed within the United States by Dornier MedTech. Our goal was to demonstrate clinical equivalence to our reusable platform and to evaluate the cost-effectiveness of a single-use digital ureteroscope. Methods: We conducted a prospective 90-day trial where all flexible ureteroscopic procedures were completed using the single-use ureteroscope. The cases were monitored for scope failure, scope deficiencies and surgeon satisfaction scores via an immediate postoperative REDCap® survey. We also performed a cost analysis between reusable scopes and the single-use ureteroscope. The cost of the reusable platform included the amortized initial purchase, maintenance and clean processing. Results: Over a 90-day period, we performed 93 flexible ureteroscopy procedures with a single-use ureteroscope, of which 74 were completed using Axis. After controlling for operating room time and disposable items used, the utilization of Axis was associated with an average reduction of 140.31 per case. Extrapolating the per-case savings over an annual case volume, we estimate a total savings of 56, 127.15. There were no disposable scope malfunctions. There were 4 (4.3%) cases converted to reusable scopes due to image quality (1), inadequate secondary deflection (2) and a tight ureter (1). Mean±SD score for image quality, mobility and ergonomics was 9.1±1.1, 8.9±1.1, 9.3±1.1, respectively. The 90-day complication rates were equal to our controls. Conclusions: We demonstrated that the Axis single-use digital ureteroscope is equivalent in function to our digital reusable scope and reduced the cost of flexible ureteroscopy.